Diagnosis and Prevalence of Chagas Disease in an Indigenous Population of Colombia - Simone Kann; Juan Carlos Dib; Andrés Aristizabal; Gustavo Concha Mendoza; Hugo Dario Soto Lacouture; Maria Hartmann; Hagen Frickmann; Lothar Kreienbrock (Microorganisms, 2022)
Chagas disease (CD) is one of the leading neglected tropical diseases. In the Americas, CD is endemic in about 21 countries, but only less than 1% of the patients have access to medical treatment. Indigenous populations are particularly affected because they live in socio-economic and climate conditions that favor CD infections. In this study, diagnostic strategies and regional prevalence of the Chagas disease were assessed. In nine villages of the indigenous tribe Wiwa, 1134 persons were tested with a Chagas-antibody-specific rapid test (RT), two different Chagas-antibody-specific ELISAs and a Chagas-specific real-time polymerase chain reaction. The overall prevalence of CD in the villages was 35.4%, with a variation from 24.9% to 52.8% for the different communities. Rapid tests and ELISAs showed the same results in all cases. The proportion of replication-active infections, defined by positive PCR results, was 8.7%. In conclusion, the assessed indigenous population in Colombia was shown to be severely affected by CD. For a serological diagnosis, one rapid test was shown to be sufficient. Replacements of ELISAs by RT would decrease costs, increase feasibility and would relevantly help detect positive patients, especially if combined with the applied real-time PCR protocol. Real-time PCR can be considered for the detection of acute cases, outbreaks, chronic cases with re-infection/activation, as well as for therapy management and control.